The original independence of the Ezra story in Ezra 7-10 and Neh 8 - Pakkala, Juha (Biblische Notizen, 2006)
This paper discusses the increasingly popular contention that the Ezra Story of Ezra-Nehemiah is a product of its present context. It would not have a history prior to its inclusion in the composition of Ezra-Nehemiah. However, this paper demonstrates the problems of this hypothesis and seeks to show that an original independence provides a better explanation for many problems that the Ezra Story has in relation to the Nehemiah Memoir and Ezra 1-6.